Combined Amelioration of Ginsenoside (Rg1, Rb1 and Rg3)-enriched Korean Red Ginseng and Probiotic Lactobacillus on Non-alcoholic Liver Disease - Kim, Jin-Chul; Jeon, Joo-Yeong; Yang, Woong-Suk; Kim, Cheorl-Ho; Eom, Dae-Woon (BENTHAM SCIENCE PUBL LTD, 2019)
Background: Red ginseng is a traditional medicine that has been used to treat numerous metabolic and inflammatory diseases. Probiotic administration has been established to have beneficial effects in non-alcoholic fatty liver disease (NAFLD). The purpose of this study was to determine whether a combination of Korean red ginseng (KRG) and probiotics could synergistically reduce NAFLD and liver inflammation compared with the effects reported for each individual product. Method: db/db and C57BL/6 mice were fed a normal chow diet and high-fat diet (HFD), respectively, and were treated with KRG, probiotics, or both. Samples were examined for lipid content, kinase protein phosphorylation, and gene expression patterns. Results: KRG- and probiotic-treated HFD-fed mice exhibited a reduction in body weight and a decrease in inflammatory cytokine secretion compared with the non-treated control mice. The same treatment was less successful in improving NAFLD parameters in the db/db mice while the combination of both products did not enhance their therapeutic potential. Conclusion: The results of this study indicate that KRG and probiotics administration ameliorated NAFLD symptoms in a mouse model of dyslipidemia by reducing weight gain and liver inflammation. Coadministration of both products did not enhance their efficacy, and further research should be conducted to clarify their mechanisms of action.
Keywords: IMMUNOMODULATORY ACTIVITY; IN-VIVO; STEATOHEPATITIS; METABOLISM; RESPONSES; INSIGHTS; PATHWAY; TARGETS; NAFLD; ACID